Transformasi Keuangan Berkelanjutan: Peran Bank Syariah dalam Mendukung UMKM melalui Green Financing dan QRIS Cross-Border - Dewi Malihatul Mawaddah; Ferry Khusnul Mubarok; Ismayadi; Ahmad Lukman Nugraha; Ubbadul Adzkiya; Tyagita Dianingtyas Sudibyo (Green Economics Review, 2024)
The transformation toward sustainable finance has become a key priority in addressing climate change and economic inequality, particularly within the Micro, Small, and Medium Enterprises (MSMEs) sector. Despite their significant contribution to national economies, MSMEs often face barriers in accessing financing that aligns with sustainability principles and digital innovation. This study aims to explore the strategic role of Islamic banks in supporting MSMEs through the implementation of green financing and the utilization of cross-border QRIS as a digital financial innovation. Using a descriptive qualitative approach, this research incorporates literature review, secondary data analysis from Islamic banks’ financial reports, and interviews with MSME actors and banking practitioners. The findings reveal that Islamic banks have substantial potential in providing sustainable financing through Sharia-compliant schemes, such as green murabahah and environmental mudharabah, which support eco-friendly MSME projects. Additionally, the integration of cross-border QRIS expands international market access for MSMEs and enhances the efficiency of cross-border transactions. The implications of this study highlight the need for strong collaboration among regulators, Islamic banks, and MSMEs to foster an inclusive and sustainable financial ecosystem. Policy recommendations include strengthening fiscal incentives for green financing, improving Sharia-based digital financial literacy, and developing payment infrastructure that supports global connectivity. Islamic banks, therefore, can act as key catalysts in driving sustainable and globally competitive MSME growth.